Challenges and solutions for using waste materials in various construction applications - Putra Jaya, Ramadhansyah; Munirwan, Reza Pahlevi; Bunyamin, Bunyamin (Popular Scientist, 2025)
The construction industry faces growing challenges in managing waste materials while striving for sustainability and resource efficiency. Incorporating waste materials into construction processes can mitigate environmental issues, reduce resource consumption, and enhance sustainability. This volume two of the Smart and Green Materials Journal explores the potential of utilizing waste materials in various construction applications, highlighting both the opportunities and obstacles associated with their integration. Key challenges include inconsistent material properties, environmental risks, and the absence of standardized guidelines for safe and effective use. Proposed solutions focus on advanced material characterization, innovative processing technologies, and the establishment of supportive policies and frameworks. By addressing these issues, the adoption of waste materials in construction can lead to reduced environmental impacts, cost savings, and the promotion of circular economy principles in the built environment.